2008
DOI: 10.1007/s10482-008-9259-6
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring a genetically modified Pseudomonas sp. released on pine leaves reveals concerted successional patterns of the bacterial phyllospheric community

Abstract: The fate of a biocontrol agent released on pine phyllosphere in a greenhouse-confined trial was followed over 102 days. The microorganism used, a Pseudomonas sp., isolated from Pinus nigra, carries the cry9a toxin gene from Bacillus thuringiensis. In order to detect the GMM, specific primers were used, and a previously defined protocol for DNA isolation from bacteria colonizing pine needles was applied. The method, based on vortexing in a suspension of glass beads followed by microcolumn extractions, allowed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Similarly, the diversity and structure of the bacterial community in the phyllosphere of a number of tree species has been described [19][20][21][22]. More than basic descriptions of community structure, 16S rRNA techniques have also been used to examine how the phyllosphere community is influenced by environmental factors, such as ultraviolet light [15] and rainfall [23], as well as pesticide [24,25] or biological control agent [16,26] application. At an ecological level, both spatial [20] and temporal [21] patterns in the composition of the phyllosphere have been examined.…”
Section: General Characteristics Of Phyllosphere Bacterial Communitiesmentioning
confidence: 99%
“…Similarly, the diversity and structure of the bacterial community in the phyllosphere of a number of tree species has been described [19][20][21][22]. More than basic descriptions of community structure, 16S rRNA techniques have also been used to examine how the phyllosphere community is influenced by environmental factors, such as ultraviolet light [15] and rainfall [23], as well as pesticide [24,25] or biological control agent [16,26] application. At an ecological level, both spatial [20] and temporal [21] patterns in the composition of the phyllosphere have been examined.…”
Section: General Characteristics Of Phyllosphere Bacterial Communitiesmentioning
confidence: 99%
“…These results suggested the potential of epiphytic bacteria modified with Bt genes for more efficient and persistent toxin delivery to the target species. We further assessed the biosafety of the transgenic Pseudomonas by first devising a procedure to optimally rescue bacteria from pine needles (Alberghini, Battisti, and Squartini 2008a) which was then tested to assess the GM strain persistence and its impact on resident phyllospheric microbiota on Pinus mugo under greenhouse conditions (Alberghini, Battisti, and Squartini 2008b). The results were reassuring in terms of biosafety as they showed that, in spite of an extended plant protection, lasting over 100 days from release, microbial communities continue to follow their natural succession and are not shifted by the effect of the biocontrol inoculant.…”
Section: Introductionmentioning
confidence: 99%